The Effect of Promotion Mix on Customers’ Decisions in Choosing Britama Savings Products at PT. Bank Rakyat Indonesia (BRI) Estimates Unit (BRI) Unit Betungan - Saputra, Radhi; Ratnawili, Ratnawili (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the influence of promotions, advertising and publicity on customer decisions in choosing Britama savings products at PT. Bank Rakyat Indonesia (BRI) Betungan Unit. Several factors will be discussed in this study, including the influence of promotions, advertising and publicity on customer decisions in choosing Britama savings products. The objects in this study were Britama savings customers at PT Bank Rakyat Indonesia (BRI), totaling 80 people. This research is a type of quantitative research. The method used in this research is descriptive method. Data collection techniques are observation, interviews and questionnaires. There are several data analysis techniques used in this study, including descriptive analysis, multiple regression analysis, coefficient of determination (R2) and hypothesis testing. The results of the study read as follows: Sales promotions have a positive effect on PT. BRI Betungan Unit thus the higher the sales promotion will increase the customer’s decision in choosing the Britama savings product at PT. Bank Rakyat Indonesia (BRI) Betungan Unit. Advertising has a positive effect on PT. BRI Betungan Unit thus the higher the advertising it will increase the customer’s decision in choosing the Britama savings product at PT. Bank Rakyat Indonesia (BRI) Betungan Unit. Publicity has a positive effect on PT. BRI Unit Betungan thus the higher the publicity it will increase the customer’s decision in choosing the Britama savings product at PT. Bank Rakyat Indonesia (BRI) Betungan Unit. Sales promotions, advertising and publicity together show an influence on customer decisions in choosing Britama savings products at PT. Bank Rakyat Indonesia (BRI) Betungan Unit.